2018
DOI: 10.1007/s12350-017-0967-z
|View full text |Cite
|
Sign up to set email alerts
|

The long way to dose reduction in myocardial perfusion imaging

Abstract: In the last decade, the concerns about radiation in myocardial perfusion imaging (MPI) have propelled the development of high-efficiency cardiac SPECT scanners, innovative collimators and iterative reconstruction algorithms with resolution recovery (IRR) for performing low-dose myocardial perfusion studies.1 However, the extent to which, using this new technology, the patient dose can be reduced is still unknown today.Several studies have shown that, using the IRR algorithms, it is possible to reduce the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Although these studies have demonstrated the potential for dose reduction in SPECT-MPI, the majority of them, if not all, have been focused on reducing the administered activity level uniformly across patients. However, the level of required dose may differ from patient to patient in order to achieve a consistent diagnostic accuracy across patients [26][27][28][29]. Some studies have shown that the amount of dose reduction should be different for obese and normal-weight patients [26], and that injected dose should depend on patient weight or body mass index (BMI) so that the acquired count statistics is maintained [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Although these studies have demonstrated the potential for dose reduction in SPECT-MPI, the majority of them, if not all, have been focused on reducing the administered activity level uniformly across patients. However, the level of required dose may differ from patient to patient in order to achieve a consistent diagnostic accuracy across patients [26][27][28][29]. Some studies have shown that the amount of dose reduction should be different for obese and normal-weight patients [26], and that injected dose should depend on patient weight or body mass index (BMI) so that the acquired count statistics is maintained [30][31][32].…”
Section: Introductionmentioning
confidence: 99%